Relevansi Filsafat Mimamsa Darsana Dalam Kehidupan Modern - Ipan Ipan; Oksan Rahmadhani; Listra Apreleliana; Yeni Lidia Setio Putri; Derson Derson; Putu Wisnu Saputra (Fakultas Dharma Duta dan Brahma Widya, 2025)
Hinduism has its own philosophical system called darsana. Darsana is interpreted as a view or philosophy that does not negate God. Darsana has several schools known as sad darsana which are included in the philosophy of astika, meaning that sad darsana is a philosophy that recognizes the authority of the Vedas. The six schools of sad darsana are Nyāya darsana, Vaiśesika darsana, Sāṁkhyā darsana, Yoga darsana, Mīmāṁsā darsana, and vedanta darsana. Mimamsa darsana is one of the sad darsana schools, mimamsa darsana is a teaching that emphasizes rituals derived from the teachings of the Vedas. In the modern era, the teachings of the teachings are challenged, namely about changes that change the way of looking at human beings to be pragmatic, meaning that everything is fast and instantaneous. This certainly threatens the relevance of the teachings of sad darsana, especially the mimamsa darsana which emphasizes the implementation of rituals. Hearing the word ritual with pragmatic human nature will certainly make the human view of ritual into something that requires long preparation and even tends to be difficult. That is what can threaten the relevance of the teachings of the darsana imamsa, therefore the focus of this paper is to see the relevance of the teachings of the darsana imamsa in the midst of this change. This paper uses a qualitative descriptive approach with a literature study method to explore the problem. The result of this article is the teaching of mim.